Origins of possession : owning and sharing in development - Rochat, Philippe, 1950- (Cambridge : Cambridge University Press, 2014)
Human possession psychology originates from deeply rooted experiential capacities shared with other animals. However, unlike other animals, we are a uniquely self-conscious species concerned with reputation, and possessions affect our perception of how we exist in the eyes of others. This book discusses the psychology surrounding the ways in which humans experience possession, claim ownership, and share from both a developmental and cross-cultural perspective. Philippe Rochat explores the origins of human possession and its symbolic development across cultures. He proposes that human possession psychology is particularly revealing of human nature, and also the source of our elusive moral sense.
Machine generated contents note: Part I. Psychology: Principles of Human Possession: 1. Experiencing possession; 2. Claiming ownership; 3. Possession and ownership transfer; 4. Symbolic spinoffs of possession; Part II. Development: Human Ontogeny of Possession: 5. First possession; 6. Ownership in development; 7. Sharing in development; Part III. Culture: Human Possession in Context: 8. Culture and possession; 9. Possession in children across cultures; Conclusion: great transformation.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Property -- Social aspects; Property -- Psychological aspects; Possessiveness; Self-actualization (Psychology); Self-actualization (Psychology) in children